2007
DOI: 10.3748/wjg.v13.i3.474
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis by endoscopic ultrasound guided fine needle aspiration of tuberculous lymphadenitis involving the peripancreatic lymph nodes: A case report

Abstract: Pancreatic tuberculosis is an extremely rare form of extrapulmonary disease. The diagnosis preoperatively is difficult because clinical, laboratory and radiologic findings are nonspecific. Published data indicate that these lesions mimic cystic neoplasms of the pancreas and the confirmation of clinical suspicion could only be obtained by an open surgical biopsy. Recently, fine needle aspiration cytology has been shown to be a safe, reliable and cost-effective alternative. We report a new case of a peripancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…On imaging, it resembles a primary malignant pancreatic tumor, and it may cause obstructive jaundice, pancreatic abscess, secondary diabetes, gastrointestinal bleeding, acute or chronic pancreatitis, and portal hypertension due to portal or splenic vein occlusion [1,[12][13][14][15]. Since specific symptoms of pancreatic tuberculosis are lacking, and there are no specific imaging findings, it is difficult to differentiate from pancreatic tumor [5,7]. Therefore, if typical pancreatic cancer cannot be diagnosed by imaging, as in the present case, pancreatic tuberculosis should be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On imaging, it resembles a primary malignant pancreatic tumor, and it may cause obstructive jaundice, pancreatic abscess, secondary diabetes, gastrointestinal bleeding, acute or chronic pancreatitis, and portal hypertension due to portal or splenic vein occlusion [1,[12][13][14][15]. Since specific symptoms of pancreatic tuberculosis are lacking, and there are no specific imaging findings, it is difficult to differentiate from pancreatic tumor [5,7]. Therefore, if typical pancreatic cancer cannot be diagnosed by imaging, as in the present case, pancreatic tuberculosis should be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was first developed in 1992, EUS-FNA has demonstrated its utility in the low-invasive definitive diagnosis of pancreatic mass lesions [20], and its usefulness in the diagnosis of pancreatic tuberculosis and peripancreatic lymph node tuberculosis has also been reported [4][5][6][7][8]. However, EUS-FNA has the potential to disseminate infection or cancer as a complication, and its casual use for lesions suspected of being resectable malignant tumors should be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…146 Peripancreatic tuberculous lymphadenopathy has also been described. 147,148 Chronic Pancreatitis Criteria in Kindreds at High-Risk for Pancreatic Cancer…”
Section: Infectious Pancreatitismentioning
confidence: 99%
“…Previous reports have shown that open surgery or laparotomy is often necessary to confirm such diagnoses (4)(5)(6). Endoscopic ultrasound-guided fine-needle aspiration biopsy (EUS-FNAB) is becoming increasingly established as a minimally-invasive alternative to open surgery for the purpose of diagnostic confirmation; more recently, the utility of EUS-FNAB in the diagnosis of pancreatic TB has also begun to be reported as well (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%